2017
DOI: 10.1186/s13174-017-0066-z
|View full text |Cite
|
Sign up to set email alerts
|

Generative models of online discussion threads: state of the art and research challenges

Abstract: Online discussion in form of written comments is a core component of many social media platforms. It has attracted increasing attention from academia, mainly because theories from social sciences can be explored at an unprecedented scale. This interest has led to the development of statistical models which are able to characterize the dynamics of threaded online conversations. In this paper, we review research on statistical modeling of online discussions, in particular, we describe current generative models o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(26 citation statements)
references
References 88 publications
(126 reference statements)
0
26
0
Order By: Relevance
“…This activity has value -for instance, citing policies on article talk pages does influence editing behavior [48] -but ingrained norms and expectations can have an effect of preventing new or underserved users from meaningfully contributing to Wikipedia [36]. In particular, Wikipedia's editor culture has a highly visible and discussed gender gap 3 . An early study found that among the 3% of site editors who self-reported gender, only 9% of edits are made by women [40].…”
Section: Background On Wikipediamentioning
confidence: 99%
See 1 more Smart Citation
“…This activity has value -for instance, citing policies on article talk pages does influence editing behavior [48] -but ingrained norms and expectations can have an effect of preventing new or underserved users from meaningfully contributing to Wikipedia [36]. In particular, Wikipedia's editor culture has a highly visible and discussed gender gap 3 . An early study found that among the 3% of site editors who self-reported gender, only 9% of edits are made by women [40].…”
Section: Background On Wikipediamentioning
confidence: 99%
“…These votes are public, signed, and timestamped. Users can also make non-voting comments, either in direct reply to the nomination, or in reply to a vote or other comments, in the standard "reply tree" model of online discussion forums [3]. AfD is highly active, with more than one third of all articles in the English-language administrative namespace Wikipedia: related to deletion debates.…”
Section: Articles For Deletionmentioning
confidence: 99%
“…They demonstrated that TRF events can create dense user communities. There have been several studies that focused on link-creation events such as triadic closure (Leskovec et al 2008), shortcuts , homophily (Hours et al 2016;Aragón et al 2017), and social influence (Aragón et al 2017). This paper formulates a retweet diffusion model based on TRF events because the events express general content sharing and link creation dynamics on Twitter.…”
Section: Related Workmentioning
confidence: 99%
“…The huge increase in the number of users of forums as time goes on have lead researchers to study the type and structure of the resulting interactions [12]. Many statistical models have been developed [13,14,15] for characterizing the dynamics of online discussions [16,17,18] and understanding the structure of threads and the resulting networks [19]. Some of them have been aiming at the prediction of the dynamics of threads and user behaviour [20,17].…”
Section: Introductionmentioning
confidence: 99%